SOSIALISASI BERHITUNG CEPAT DENGAN TEKNIK FIVE FINGER DI RA AL ASHRIYAH KOTA LANGSA - Wiwin Apriani; Syariani Br. Tambunan; Hendra Susanto; Ema Julianda (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of this community service activity was motivated by the low counting ability of the early childhood, as well as the lack of interest and motivation of children in fast counting. Thus, there were desires to know and examine children's numeracy abilities using the five finger method with learning media using their own body parts. The participants in this activity were 20 students of RA Al Ashriyah, Langsa City. The purpose of this activity was to foster interest and talent in preschool children in fast counting using the five finger method. The results of this socialization activity showed that the numeracy skills of RA Al Ashriyah children in Langsa City using the five finger method had increased compared to children who counted conventionally. This was seen when given practice questions, most of the children can quickly calculate the answers properly and correctly. This activity can also train children's quick counting skills by familiarizing children with learning simple things. In addition, this activity can increase children's creative thinking in utilizing objects around them as learning media.